RADIOMEASURING TEMPERATURE CONVERTER - Osadchuk, Volodymyr; Osadchuk, Oleksandr; Baraban, Sergii (Scientific Works of Vinnytsia National Technical University, 2015)
The paper presents and describes the radiomeasuring temperature converter on the basis of transistor structure with negative resistance; there had been made a computer experiment of devise’s circuit operation; there had been determined the function of conversion and function of sensitiveness of radiomeasuring temperature converter; there had been conducted the experimental researches of operation of temperature device.